2020
DOI: 10.1186/s13071-020-04193-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex PCR for simultaneous genotyping of kdr mutations V410L, V1016I and F1534C in Aedes aegypti (L.)

Abstract: Background: Knockdown resistance (kdr) is the main mechanism that confers resistance to pyrethroids and DDT. This is a product of non-synonymous mutations in the voltage-gated sodium channel (vgsc) gene, and these mutations produce a change of a single amino acid which reduces the affinity of the target site for the insecticide molecule. In Mexico, V410L, V1016I and F1534C mutations are common in pyrethroid-resistant Aedes aegypti (L.) populations. Methods: A multiplex PCR was developed to detect the V410L, V1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…Indeed, 81.8% of all females genotyped had at least one resistant allele at the 410 position ( Table 2 and Figs 1 and 2 ). These results match previous studies which had found high frequencies of the V410L genotype in combination with V1016I and F1534C genotypes throughout the world, including the Americas and Africa [ 20 , 26 28 , 45 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, 81.8% of all females genotyped had at least one resistant allele at the 410 position ( Table 2 and Figs 1 and 2 ). These results match previous studies which had found high frequencies of the V410L genotype in combination with V1016I and F1534C genotypes throughout the world, including the Americas and Africa [ 20 , 26 28 , 45 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…For the genotyping assay for polymorphisms V1016G/I, F1534C, and V410L, mosquito extracted DNA was investigated by AS-qPCR. Published primer mixes were used consisting of a common reverse primer and two specific primers targeting each polymorphic site [ 44 46 ]. The specificity of the primers was attained for the 3’-end.…”
Section: Methodsmentioning
confidence: 99%
“…Cycling conditions for V1016G consisted of a first denaturing step of 94°C for 10 min, then denaturing 94°C for 30 seconds, annealing time of 55°C for 30 sec, and elongation time of 72°C for 30 seconds for 40 cycles [ 45 ]. Cycling conditions for V410L consisted of a first denaturing step of 95°C for 10 min, then denaturing 95°C for 1 min, annealing time of 56°C for 20 sec, and elongation time of 72°C for 20 seconds for 40 cycles [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Kajian resistensi vektor terhadap insektisida dengan teknik impregnated paper telah menunjukkan keberhasilan, 31,32 demikian juga dengan teknik molekuler, baik pada vektor malaria maupun DBD. [33][34][35][36] Sebab itu, pendekatan-pendekatan tersebut patut diaplikasikan dalam penentuan resistensi insektisida.…”
Section: Pembahasanunclassified